Selenium‐Catalyzed C(sp3)H Acyloxylation: Application in the Expedient Synthesis of Isobenzofuranones. Issue 19 (23rd March 2015) - Krätzschmar, Felix; Kaßel, Martin; Delony, Daniel; Breder, Alexander
Abstract: Oxidative Se‐catalyzed C(sp 3 )H bond acyloxylation has been used to construct a diverse array of isobenzofuranones from simple ortho ‐allyl benzoic acid derivatives. The synthetic procedure employs mild reaction conditions and gives high chemoselectivity enabled by an inexpensive organodiselane catalyst. The presented approach offers a new synthetic pathway toward the core structures of phthalide natural products. Abstract : Allylic oxidation revisited : Oxidative intramolecular C(sp 3 )H acyloxylation of allylated benzoic acid derivatives through selenium catalysis is reported. This protocol provides direct access to the isobenzofuranone skeleton, a structural motif frequently found in phthalide natural products, in yields of up to 81 % using N ‐fluorobenzenesulfonimide (NFSI) as the terminal oxidant.